2010
DOI: 10.1097/mlr.0b013e3181d559b4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic, Pharmacy-Based, and Self-Reported Health Measures in Risk Equalization Models

Abstract: It is concluded that the self-reported health measures make an independent contribution to forecasting health care expenditures, even if the prediction model already includes diagnostic and pharmacy-based information currently used in Dutch risk equalization models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Extensive literature demonstrates a link between various diagnosisbased and prior utilization-based measures of complexity, acute care utilization, and costs. [19][20][21][22][23][29][30][31][32] Generally, these approaches use administrative claims/billing, and less commonly, electronic medical record data to create risk groupings that predict future utilization and costs. [33][34][35] More limited literature demonstrates that adding outpatient utilization information and psychosocial factors improve predictive models for acute care utilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive literature demonstrates a link between various diagnosisbased and prior utilization-based measures of complexity, acute care utilization, and costs. [19][20][21][22][23][29][30][31][32] Generally, these approaches use administrative claims/billing, and less commonly, electronic medical record data to create risk groupings that predict future utilization and costs. [33][34][35] More limited literature demonstrates that adding outpatient utilization information and psychosocial factors improve predictive models for acute care utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Current quantitative methods for identifying the complex patients at highest risk for suboptimal future clinical quality and utilization outcomes rely primarily on diagnosis-based and utilization-based algorithms to predict future utilization. [13][14][15][16][17][18][19][20][21][22][23] These tools miss clinical characteristics that are not present in billing data and may not capture non-clinical contributors to patient complexity.…”
Section: Introductionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t Initial studies found that demographics alone have very low predictive power [10]. The introduction of diagnosis cost group/hierarchical conditions categories (DCG/HCC) greatly improves the predictive power compared to models that use sex and age alone as independent variables [24].…”
Section: Discussionmentioning
confidence: 99%
“…Others are based on diagnoses: Clinical Risk groups (CRGs) [6,7], Adjusted Clinical Groups (ACGs) [8] and Diagnostic Cost Groups, (DCG). Finally there are the mixed models that combine both -Diagnostic Cost Groups, (DCG/Rx) [9] and Adjusted Clinical Groups (ACG/Rx) [10].The usefulness of these models is especially relevant for integrated health systems such as National Health Systems. These tools described above also allow stratification of the population according to morbidity, which permits patients with the greatest risk to benefit from case management programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Some models combining medicine code and diagnoses, Diagnostic Cost Groups, DCG/Rx [14] and Adjusted Clinical Groups ACG/Rx [15,16], have proven their efficacy, but need diagnoses accuracy information that is not always available.…”
Section: Adjusting Pharmaceutical Expenditure Backgroundmentioning
confidence: 99%